Intercultural Childbirth: Impact on the Maternal Health of the Ecuadorian Kichwa and Mestizo People of the Otavalo Region - Matute, Susana Eulalia Dueñas; Martinez, Edson Zangiacomi; Donadi, Eduardo Antônio (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective Considering the increased frequency of maternal deaths reported from 2001 to 2005 for Indigenous and mestizo women from the Ecuadorian rural area of Otavalo, where the Kichwa people has lived for centuries, the objective of the present article is to describe how the efforts of the local health community and hospital workers together with a propitious political environment facilitated the implementation of intercultural childbirth, which is a strategy that respects the Andean childbirth worldview.Methods We evaluated a 3-year follow-up (2014–16) of the maternal mortality and the childbirth features (4,213 deliveries).Results Although the Western-style (lying down position) childbirth was adopted by 80.6% of the pregnant women, 19.4% of both mestizo and Indigenous women adopted the intercultural delivery (squatting and kneeling positions). Both intercultural (42.2%) and Western-style (57.8%) childbirths were similarly adopted by Kichwa women, whereas Western-style childbirth predominated among mestizo women (94.0%). After the implementation of the intercultural strategy in 2008, a dramatic decrease of maternal deaths has been observed until now in both rural and urban Otavalo regions.Conclusion This scenario reveals that the intermingling of cultures and respect for childbirth traditions have decreased maternal mortality in this World Health Organization-awarded program.
Keywords: maternal mortality; intercultural childbirth; Kichwa; Otavalo; Ecuador